Forecasting Equity Premium with Technical and Macroeconomic Indicators - Lehti, Emil (My University, 2023)
This thesis investigates the forecasting of the equity premium, a critical metric in financial economics, representing the difference between the expected return on a stock market portfolio and the risk-free rate. Accurate equity premium forecasts are paramount for asset allocation, risk management, and financial market regulation. While financial theory posits that stock prices should align with future discounted cash flows, empirical forecasting remains challenging. In this study, a variety of forecasting methods and variables are assessed for their ability to predict the equity premium. The review of recent literature highlights the crucial role of model selection and parameterization in predicting the equity premium. The study acknowledges the contribution of alternative model specifications, which address model uncertainty and parameter instability. These models have demonstrated their potential to yield statistically and economically significant forecasts, outperforming the historical average forecast. The thesis corroborates the literature, suggesting that forecasting during recessions yields superior results compared to the historical average, while forecasting during expansion periods poses a greater challenge. This research conducts a meticulous examination of macroeconomic predictors and technical indicators, utilized within diverse model specifications, to forecast the equity premium using updated data. Established macroeconomic predictors and technical indicators often fail to produce statistically or economically significant forecasts during expansion periods. Nevertheless, when macroeconomic predictors are employed within multiple-predictor models, investors can realize benefits surpassing those of the historical average forecast. During recessions, forecasting is comparatively less challenging, with technical indicators delivering the best forecasts both statistically and economically. Owing to the inherent stability of technical indicators, their incorporation into multiple-predictor models doesn't yield any additional value. This study puts forth a strategic recommendation to enhance the economic advantage of equity premium forecasts. It suggests that an optimal approach could involve the deployment of multiple-predictor models that use macroeconomic predictors during periods of economic expansion, and individual technical indicators during recessions. This contribution to the discourse on equity premium forecasting advocates for a state-dependent forecasting methodology. Future research could explore this state-dependent forecasting methodology further. This could involve the development and rigorous testing of state-dependent forecasting models, as well as the identification of the most suitable predictors for each economic state. While forecasting during recessions appears to be easier, it could be beneficial to examine different benchmark models depending on the current state of the economy. The widely used benchmark in current literature, the historical average model, consistently predicts positive equity premiums, even though these are generally negative in reality during recessions. Therefore, it might be prudent to develop a benchmark model that also depends on the state of the economy and compare the generated state-dependent forecasts to this model. This approach could provide a more accurate comparative measure for evaluating forecasting strategies during different economic conditions.

Tässä tutkielmassa tarkastellaan osakemarkkinoiden tuotto-odotuksen ja riskittömän korkotuoton välistä eroa eli osakepreemion ennustamista. Tarkat osakepreemio -ennusteet ovat keskeisiä varainhoidossa, riskienhallinnassa ja rahoitusmarkkinoiden sääntelyssä. Vaikka rahoitusteorian, mukaan osakekurssien tulisi vastata tulevaisuuden diskontattuja kassavirtoja, osakepreemion empiirinen ennustaminen on haastavaa. Tässä tutkimuksessa arvioidaan erilaisten ennustusmenetelmien ja muuttujien kykyä ennustaa osakepreemiota. Kirjallisuuskatsaus korostaa mallin valinnan ja parametrisoinnin olevan keskeisessä roolissa osakepreemiota ennustettaessa. Tutkimus tunnustaa vaihtoehtoisten mallisääntöjen merkityksen, jotka käsittelevät mallin epävarmuutta ja parametrien epävakautta. Näiden mallien on osoitettu pystyvän tuottamaan historiallista keskiarvoa tarkempia ennusteita niin tilastollisesti kuin taloudellisesti merkitsevästi. Tutkielma tukee kirjallisuutta, jonka mukaan taantumissa ennustaminen on suhteessa helpompaa verrattuna historialliseen keskiarvoon, kun taas laajentumiskausina ennustaminen on haastavampaa. Tutkimuksessa tarkastellaan makrotaloudellisia ennustajia ja teknisiä indikaattoreita, joita käytetään sekä yksittäisinä ennustajina että laajemmissa ennustemalleissa, joita käytetään osakepreemion ennustamiseen päivitetyllä aineistolla. Vakiintuneet makrotaloudelliset ennustajat ja tekniset indikaattorit eivät usein pysty tuottamaan tilastollisesti tai taloudellisesti merkitseviä ennusteita talouden nousukausina. Kuitenkin, kun makrotaloudellisia ennustajia käytetään laajemmissa ennustemalleissa, sijoittajat voivat saavuttaa taloudellisia etuja verrattaessa ennusteiden muodostamiseen historiallisen keskiarvon mukaisesti. Taantumissa ennustaminen on helpompaa, ja tekniset indikaattorit tuottavat tarkimmat ennusteet sekä tilastollisesti että taloudellisesti. Teknisten indikaattorien luontaisen vakauden vuoksi niiden käyttö laajemmissa ennustemalleissa ei tuota lisäarvoa. Erityisesti taantumissa on perusteltua käyttää teknisiä indikaattoreita itsenäisinä osakepreemion ennustajina. Tutkielman mukaan optimaalinen lähestymistapa osakepreemion ennustamiseen on teknisten indikaattorien käyttö taantumissa ja makrotaloudellisten ennustajien käyttö laajemmissa ennustemalleissa talouden nousukausina. Tämä kannustaa tarkastelemaan osakepreemion ennustamista tilariippuvaisilla ennustemenetelmillä. Katsoen eteenpäin, tulevat tutkimukset voisivat tutkia tätä tilasta riippuvaa ennustusmenetelmää tarkemmin. Tämä voisi sisältää tilasta riippuvien ennustusmallien kehittämisen ja perusteellisen testaamisen, sekä sopivimpien ennustajien tunnistamisen kullekin taloudelliselle tilalle. Nykyisessä kirjallisuudessa laajalti käytetty vertailumalli, historiallinen keskiarvo, ennustaa jatkuvasti positiivisia osakepreemioita, vaikka todellisuudessa taantumissa osaketuotot, ja osakepreemiot ovat negatiivisia. Siksi saattaisi olla mielekästä tarkastella ennusteita eri vertailumallilla, joka myös riippuu talouden tilasta. Tämä lähestymistapa voisi tarjota tarkemman vertailumittarin ennustestrategioiden arvioimiseksi eri taloudellisissa olosuhteissa.
Keywords: equity premium forecasting, technical indicators, macroeconomic predictors, business cycle, osakepreemion ennustaminen, tekniset indikaattorit, makrotaloudelliset ennustajat, suhdannevaihtelu